Analisis Kelayakan Usaha Pembesaran Ikan Gabus Haruan (Channa striata Bloch) Dalam Karamba Jaring Tancap Di Desa Bangkau Kecamatan Kandangan Kabupaten Hulu Sungai Selatan Kalimantan Selatan - Khalid Darda; Idiannor Mahyudin; Emmy Sri Mahreda; Indira Fitriliyani (EnviroScienteae, 2019)
The purpose of this study was to identify the business problems of cultivating striped snakeheads (Channa striata Bloch) in embedded net cages, analyze the feasibility of the business of cultivating striped snakeheads in net cages and identify the assumptions/perspectives of the impacts of striped snakehead farming in embedded net cages on environmental aspects. This study was survey research. Location determination in Bangkau Village, Kandangan Subdistrict was done purposively because this area was a center for cultivating striped snakeheads in Hulu Sungai Selatan Regency. The collection of respondent data in this village was carried out in a census of 20 people from the whole population of cultivated striped snakeheads in embedded net cages. The identification of problems that occurred in the business of cultivating striped snakeheads in embedded net cages was done by descriptive analysis in the field. The analysis used was the calculation analyze business feasibility used the analysis of Net Present Value (NPV), Net Benefit Cost Ratio (Net BCR) and Internal Rate Return (IRR), while to know the effect on environmental aspects, it was done by identifying and analyzing the description of population rescue. The results showed that the farmers’ problems were the lack of availability of seeds, the fluctuations in the selling price of fish and domestic fish, which could be attacked by scabies. The business of cultivating striped snakeheads in embedded net cages in Bangkau Village, Kandangan Subdistrict, Hulu Sungai Selatan Regency was feasible to be carried out in accordance with the results of analysis namely Net Present Value 4,943,337, Net Benefit Cost Ratio (Net BCR) 2.29 and Internal Rate Return (IRR ) amounting to 51.53%. This effort influences the assumption of rescuing striped snakehead fish populations from this cultivation is 48.75%.